2017
DOI: 10.21873/invivo.11082
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Non-small Cell Lung Cancer with Solitary Hematogenous Metastases

Abstract: Abstract. Background Stage IV disease at initial presentation accounts for approximately 41% of newly-diagnosed cases with non-small cell lung cancer (NSCLC) (1). Prognosis for metastatic lung cancer remains dismal, despite continuously emerging treatment options. Although the majority of patients have disseminated metastatic disease at diagnosis, a small percentage are found to have a solitary metastasis. In addition any patients with NSCLC who previously received definitive treatment may experience metachron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Metastasectomy is considered a beneficial treatment for patients with pulmonary metastases whose primary tumor has been well controlled, and pulmonary resection has been shown to be beneficial for patients with resectable and isolated pulmonary metastases (6). However, few studies have reported such results for pulmonary metastasectomy for PDAC, probably because of their extremely poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastasectomy is considered a beneficial treatment for patients with pulmonary metastases whose primary tumor has been well controlled, and pulmonary resection has been shown to be beneficial for patients with resectable and isolated pulmonary metastases (6). However, few studies have reported such results for pulmonary metastasectomy for PDAC, probably because of their extremely poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…And recently, Karagkiouzis et al (6) reported that combined surgical resection of primary non-small cell lung cancer and solitary hematogenous metastasis might be associated with improved survival. Recurrent PDAC, in comparison, has been notoriously difficult to manage surgically as it is typically characterized by aggressive growth, a multifocal pattern of recurrence, and technically unresectable disease (7).…”
mentioning
confidence: 99%
“…Extrathoracic metastases, which were an M1b descriptor in the seventh edition of the TNM staging system, are now divided into M1b and M1c descriptors in the eighth edition of the TNM staging system. Patients with a single extrathoracic metastatic lesion in a single organ (M1b) have better survival rates than those with multiple extrathoracic lesions (M1c) and may be candidates for surgical resection or local ablative therapy (18).…”
Section: Descriptorsmentioning
confidence: 99%
“…Finally, Karagkiouzis et al examined 12 extrapulmonary oligometastatic patients with NSCLC; adrenal metastasis was common (n = 6, 50%) followed by brain metastasis (n = 3, 25%), thoracic wall metastasis (n = 2, 16.7%), and diaphragm (n = 1, 8.3%) [26]. All patients underwent combined resections of the primary lung tumor and solitary hematogenous metastasis; subsequently all patients received adjuvant chemotherapy, and the median follow-up period was 13.5 months [26].…”
Section: A General Considerationmentioning
confidence: 99%
“…All patients underwent combined resections of the primary lung tumor and solitary hematogenous metastasis; subsequently all patients received adjuvant chemotherapy, and the median follow-up period was 13.5 months [26]. The median survival was 24.1 months, survival rates at 1-and 5-years were 73%, and 39%, respectively [26].…”
Section: A General Considerationmentioning
confidence: 99%